Srategi Peningkatan Penerimaan Pajak Bea Perolehan Hak Atas Tanah Dan Bangunan (BPHTB) Di Kabupaten Seluma - Rahiman Dani; Wahyudi Saputra; Dodo Sutardi; Henny Aprianty; Heru Purnawan (Perkumpulan Dosen Muda (PDM) Bengkulu, 2023)
The ideals of regional autonomy to achieve regional independence have not been realized. Therefore, the ideals of regional autonomy to achieve regional independence have not yet been realized. In Seluma District, the capacity of local own-source revenues to support the APBD is still unstable. Seluma Regency's PAD is still low and tends to decrease. The purpose of this research is to find out and understand a detailed description of the internal and external conditions faced by the Regional Treasury Board of Seluma Regency to increase BPHTB tax revenues in Seluma Regency. The research method used to achieve the research objectives is a qualitative descriptive method. Interview, observation, and documentation methods were used to collect data with 5 informants at the regional tax office of Seluma Regency, BPN, a notary, and a regional bank. Data analysis using SWOT analysis. The results of the study show that 1) the current organizational situation offers enormous opportunities, but on the other hand the organization also has some internal limitations/weaknesses. In the current situation, the tax office must be able to minimize internal organizational problems to take better advantage of opportunities. 2) External and internal environmental conditions In applying BPHTB tax rates, several appropriate strategies have been formulated to increase BPHTB revenues in Seluma Regency.Â